Pengaruh Dimensi Mutu Pelayanan Keperawatan Terhadap Kepuasan Pasien di RS PKU Muhammadiyah Mayong Jepara - Titik Sumarni; Sudiro Sudiro (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2019)
In PKU Muhammadiyah Mayong Jepara Hospital, in 3 years from 2013, 2014, and 2015 the number of patient dissatisfaction with nurse services was 20.5%, 22.6% and 25% respectively. According to Parasuraman et al. 5 dimensions of service quality that affect satisfaction are reliability, assurance, tangible, empathetic and responsiveness. The purpose of this study was to determine the effect of the dimensions of nursing service quality on patient satisfaction in the Inpatient Installation of PKU Muhammadiyah Hospital in Mayong Jepara.This type of research is quantitative, with observational studies and uses a cross sectional approach. Data collection through surveys using a structured guided questionnaire in filling out questionnaires through interviews. The population of objects are 300 patients include 4 rooms. The inclusion criteria were patients who were returning home, the patient had been treated for 3 days, and the patient was 18 years old up to 60 years old. Exclusion criteria were VIP room patients, HCU chambers, isolation rooms, infants and children (less than 18 years), and elderly patients (over 60 years). The number of samples counted 75, the variables measured are 5 dimensions of service quality. Data were processed through univariate procedure with percentage, bivariate with pearson product momment.The results obtained from the responses of respondents in getting the lowest mean value is responsiveness, where all dimensions of service quality are related to patient satisfaction (p value <0.05). The strongest relationship is reliability.Recomendation: the nurse immediately handles the patient and provides quick response during the inpatient ward.